Entrepreneurship: toward the Nirvana state of rest - Packard, Mark (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
In this paper, we reconsider the various states of rest within Austrian market process theory. While this theory certainly embodies a superior representation of market processes to the neoclassical general equilibrium theory, it falls short of producing a holistic theory of human action. The analysis left out those human actions that produce changes to the so-called ‘final state of rest,’ which have so far been taken as exogenous to the market process. These exogenous shocks include knowledge generation and preference shifting. However, I argue that these can and ought to be understood as market phenomena, and so belong within the scope of praxeological analysis. To capture these types of human action, I propose that a new and truly ‘final’ state of rest be introduced, which we term the ‘nirvana state of rest.’ This new state represents a ‘true’ final state, in which human action ceases because all needs, and thus all motivation to act, are completely and perpetually assuaged. Introducing this state into the analysis, we can break free from myopic analyses of mere present states of knowledge and values to observe and explain general tendencies in market processes, prices, and entrepreneurship. I also show how quarrels within Austrian circles might be resolved through this expanded, macroscopic lens.